Molecular Docking Study on COVID-19 Drug Activity of N-(2-phenylethyl)methanesulfonamide Derivatives as Main Protease Inhibitor - Purwaniati - Purwaniati (Universitas Islam Negeri Alauddin Makassar, 2020)
The aim of this research is to find potential new compounds that are potential to be developed as COVID-19 drugs with a mechanism to inhibit the main protease (Mpro) enzyme from the COVID-19 virus. The method used molecular docking with the AutodockTools 1.5.6 program and continued with the prediction of pharmacokinetic profiles and toxicity with the help of the PreADMET application. Inhibition potential was assessed based on the binding energy value and the inhibition constant. Research showes that natural ligand (N-(2-phenyl-ethyl) methanesulfonamide), S1, S3, S7, and S9 were compounds that provide inhibitory activity against Mpro enzymes which were more potent than lopinavir as a comparison. The binding energy and inhibition constants of natural ligands, S1, S3, S7, and S9 are lower than comparative compounds, respectively -1.61 kcal/mol and 66.26 mM. ADMET prediction shows that these potential compounds still need improvement in terms of pharmacokinetics and toxicity.